The effect of pressure on hydrogen solubility in Zircaloy-4 - Weekes,H; Dye,D; Proctor,JE; Smith,DS; Simionescu,C; Prior,TJ; Wenman,M (Journal of Nuclear Materials, 2019)
The effect of pressure on the room temperature solubility of hydrogen inZircaloy-4 was examined using synchrotron X-ray diffraction on small groundflake samples in a diamond anvil cell at pressures up to 20.9 GPa. Differentcombinations of hydrogen level/state in the sample and of pressure transmittingmedium were examined; in all three cases examined, it could be concluded thatpressure resulted in the dissolution of d hydrides and that interstitialhydrogen retards the formation of w Zr. A pressure of around 9 GPa was requiredto halve the hydride fraction. These results imply that the effect of pressureis thermodynamically analogous to that of increasing temperature, but that theeffect is small. The results are consistent with the volume per Zr atom of thea, d and w phases, with the bulk moduli of a and d, and with previousmeasurements of the hydrogen site molar volumes in the a and d phases. Theresults are interpreted in terms of their implication for our understanding ofthe driving forces for hydride precipitation at crack tips, which are in aregion of hydrostatic tensile stress on the order of 1.5 GPa.